Incorporating project-based language learning into distance learning: Creating a homepage during computer-mediated learning sessions. (May 2023) - Kato, Fumie; Spring, Ryan; Mori, Chikako
This quasi-experimental study reports on the outcomes of a video-synchronous learning program in which an element of project-based foreign language learning was integrated. The project chosen was to cooperatively create a homepage. American students learning Japanese in the United States and Japanese students learning English in Japan made pairs and communicated in both their native and target languages via Skype to complete the project. The goals of this educational program were to increase intrinsic motivation in learners and improve their target language oral abilities, and identify challenges and problems with implementation. The program was conducted during the spring semester in 2017 and evaluated both quantitatively (via pre- and posttests) and qualitatively (via surveys and reflection papers). The results show that both groups of students had improved their mean length of utterance in their target language, a strong indicator of increased speaking ability. Furthermore, qualitative analysis showed their motivation levels increased as compared to previous similar programs. Although the majority of the students were interested in creating a homepage, there were some technical problems with the homepage creation software.